JILBAB DALAM AL-QUR’AN: (Studi Komparasi Tafsir al-Misbah dan Tafsir al Munir) (At-Tibyan, 2023)
This research is motivated by the emergence of differences in understanding of the hijab. One of the Indonesian mufassirs Quraish Shihab in this case becomes pros and cons over his interpretation of the hijab that seems to provide space for those who do not require the hijab in his tafsir, in contrast to one of the mufassirs from the Middle East Wahbah az-Zuhaili who contradicts the opinion of Quraish Shihab. Therefore, researchers are interested in comparing the two scholars. This research is a library research. With qualitative type by using Muqarran approach. Muqarran method is comparing (comparative or comparative) where in this study will compare something of the same feature, which is often used to help explain a principle or idea. The results of this study found some similarities and differences in the interpretation of the hijab verse in Surah al-Ahzab verse 59 and an-Nur verse 31 between Quraish Shihab and Wahbah az-Zuhaili.  Their interpretation both use Tahlili method, with Wahbah az-Zuhaili Fiqh interpretation style and Quraish Shihab with Adabi Ijtima'i style.  Then the similarity in interpreting the verse above is that both of them are of the opinion that the command to use the hijab is for all Muslim women. While the difference is about the limits of its use or what can be seen. Quraish Shihab does not limit what can be seen